The Effect of Robotics Experiments on the Scientific Literacy of Junior High School Students in Bengkulu Province - Mayub, A.; Setiawan, A.; Fahmizal, F.; Wardaya, R. W.; Lazfihma, L; Johan, H.; Nursaadah, E. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
This research describes students' scientific literacy, motivation to learn science, and science teachers' responses after participating in the